Association Between Work-Relate Musculoskeletal Disorder and Ergonomic Risk Factors Among Nursing Professionals in Ranya and Qaladiza Districts - Khudhir, Karwan Mahmood; Saleh, Kochar Khasraw; Qadir, Muhammed Saeed; Mahmood, Kochr Ali; Ariffin, Ahmad Azuhairi (Kurdistan Journal of Applied Research, 2017)
Work related musculoskeletal disorders (WRMSDs) represent one of the leading causes of occupational injury and disability among the professional nursing, due to the number and variety of risk factors associated with the work environment. This study was carried out to determine the prevalence of work related musculoskeletal disorders (WRMSDs) and its association with ergonomic risk factors. A self-administered questionnaire and observational method was used to collect information from 420 individuals and then the data were computerized and analyzed by using SPSS version 21. The overall prevalence of WRMSDs among Ranya and Qaladiza districts nurses was 74%. The neck pain was the most prevalent site of WRMSDs (48.4%) compared to other body parts. Logistic regression analysis indicated that significant risk factors for WRMSDs symptoms were older nurses aged >39.5 years old (OR=3.076, 95% CI: 1.200, 7.884), medium RULA risk level (OR= 255.096, 95% CI: 24.078, 2702.681), very high RULA risk level (OR=151.675, 95% CI: 17.536, 1311.891), low RULA risk level (OR=9.277, 95% CI: 1.064, 80.893). Prevention strategies and health education which emphasizes on psychosocial risk factors and how to improve working conditions should be introduced.